Panem nostrum quotidianum da nobis hodie - Iria Gonçalves (Medievalista)
The Europeans of the Middle Ages have always valued bread within their food system, especially as meat, another highly valued food, became scarcer. But by tradition, more than a thousand years old, in Europe and the Mediterranean, bread was the food par excellence, the only one that the faithful asked God for in their prayers because it was the one whose lack meant hunger. Grain was grown everywhere, but this didn't stop times of scarcity and famine, both in the countryside and in the cities. While the latter had other means of responding to these crises and these phenomena have been better studied there, we barely know how rural people reacted to such adversities. The response of the rural world to the cereal crisis of 1438-1440 is analyzed through a book containing the accounts of the monastery of Alcobaça for the years 1437-1440. This is clearer for the monastery, since the peasants' reactions are more difficult to discern, as they are filtered through the eyes of the landlord. In 1439, the reduction of two-thirds in the abbey's cereal revenues was countered by the cultivation of target maize, a spring cereal that could replace wheat and barley. But the crisis had other effects, such as spiraling grain prices, rising flour extraction rates and a decline in the quality of daily bread, or the resort to substitute foods. From monks to peasants, everyone felt the consequences of this crisis, albeit on very different scales and in very dissimilar ways.